THE FREQUENCY DISTRIBUTION OF CENTRAL MODAL VERBS IN KURIKULUM MERDEKA’S TEXTBOOKS IN INDONESIA: A CORPUS-BASED ANALYSIS - Akhofullah; Ikmi Nur Oktavianti (PROJECT (Professional Journal of English Education), 2023)
This study focuses on investigating the central modal verbs used in Kurikulum Merdek’s Textbooks in Indonesia. This study uses corpus-based analysis and categorizes it as descriptive qualitative research. The data sources are three series of Kurikulum Merdeka's textbooks for senior high school level in Indonesia. In supporting the investigation of linguistic features presented in the textbooks, this study uses the Corpus of Contemporary American English (COCA) and British National Corpus (BNC) as the control corpora to represent real language data. The result of this study shows that“can,” “will,” and “would” are the most frequently central modal verbs in the COCA, BNC, and kurikulum merdeka’s textbooks, while the least frequent central modal verbs used among those three sources is “shall. However, “would” is not significant present in the textbooks compared to that in COCA and BNC. Moreover, the rest of the central modal verbs vary among the three sources, like “must’ and “may.”